Pharmacoeconomic analysis of antimicrobials at the intensive care unit in a tertiary hospital (Research, Society and Development, 2020)
Antimicrobials are used to inhibit or fight the growth of certain microorganisms and, therefore, they are widely used in the intensive care unit. Pharmacoeconomics is used to improve the use of financial resources, taking the cost-effectiveness of treatment into account. The objective of this work was to analyze the consumption of antimicrobials, identifying the most expensive and most used, in addition to verifying the therapeutic class of greatest consumption. This is a retrospective study with a quantitative approach, carried out from January 2019 to May 2019 in a tertiary hospital. The data were obtained from the forms of use of restricted medications and the database of the hospital. These were recorded in a Microsoft Office Excel 2016® spreadsheet and the expense with antimicrobials was calculated by multiplying the number of units dispensed by the unit price in reais. The analysis of descriptive statistics occurred through the calculation of frequency and percentage. In the period analyzed, 10,286 units of antimicrobials were consumed, corresponding to a total cost of R$ 269,265.94 reais. The most expensive drugs were, respectively, piperacillin + tazobactam, meropenem and linezolid; the most consumed were meropenem, piperacillin + tazobactam and vancomycin, respectively. The classes with the highest consumption were, respectively, carbapenems, penicillin and glycopeptides. From the results, it was verified that the consumption of antimicrobials in the intensive care unit generates a high financial impact on the hospital, in addition to the fact that the most consumed antimicrobials that generated the highest costs were those of broad-spectrum.